Flipbook Berdiferensiasi Materi Aku dan Lingkungan Sekitarku Berlandaskan Tri Hita Karana untuk Siswa Sekolah Dasar - Gede Aditya Wiguna; I G Agung Jaya Suryawan; I Ketut Ngurah Ardiawan (Walada: Journal of Primary Education, 2026)
Conventional, monotonous, and uniform learning approaches in elementary schools often fail to accommodate diverse student learning styles and lead to a decline in ecological awareness regarding environmental topics. This study aims to develop an innovative media in the form of a differentiated digital flipbook on the topic "Me and My Surrounding Environment" based on the Tri Hita Karana philosophy for fifth-grade elementary school students. (2) Methods: This study applied the Research and Development (R&D) method using the ADDIE development model. Data were collected through closed-ended questionnaires from expert validators, classroom teachers, and students, which were then analyzed using descriptive quantitative techniques and the Aiken’s V Validity coefficient. (3) Results: The validity test conducted by nine experts indicated that the product met highly valid qualifications, achieving Aiken's V indexes of 0.96 (content), 0.91 (media), and 0.97 (language). Furthermore, the field practicality test yielded identical scores of 96% from both teacher and student responses, placing it in the highly practical category. (4) Implications: This interactive digital media serves as an effective, inclusive instructional solution to accommodate various student learning modalities (visual, auditory, kinesthetic) within a single platform while contextually internalizing character values of environmental care based on local wisdom